PREDIKTOR DISPOSISIONAL ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AGEN ASURANSI DAN MANAJER (STUDI PADA PERUSAHAAN ASURANSI DI JAWA TENGAH) - Irmawati Irmawati; Berta Bekti Retnawati (STIE Pelita Nusantara Semarang, 2018)
Some variales in the organizational behavior that greatly affect the performance of employees are productivity, absenteeism, turnover, and job satisfaction, deviant behavior in the workplace and Organizational Citizenship Behavior. When associated with the empirical situation in business, in the field of insurance the role of sales force (insurance agent) becomes very important for the company. This profession requires the sales force to move closer to prospective customers both individuals and corporates. Their job is as corporate ambassadors / someone who is trusted to represent the company to promote, offer, and explain insurance products professionally, credibly and integrity. This study aims to examine the OCB dispositional predictors of both insurance agents and managers. This research can contribute thoughts to the managerial practices of insurance industry business actors in improving organizational performance from Organizational Citizenship Behavior (OCB). The results of the analysis show that the OCB-I diagnostic model with the highest indicator is always willing to help customers and office guests who need help, then willing to help new employees to adapt to the work environment even though not ruled boss and as much as possible always keep up with the developments and changes that occur in the organization . Meanwhile the category that has an average score of four under the answer is willing to help ease the work of overloaded co-workers and the lowest is always complaining when there is a less ideal situation in the workplace. Basically, the agent's job is to find and maintain customers, agents work under supervisor and they can work in groups or independently. Group work is usually done by new agents who join the company, they follow the group as their place of learning in acquiring clients or customers. Experienced agents will be appointed as group leaders and manage the agents who are members. In this case the behavior of OCB-I can indicate an agent or group leader helps each other to achieve their target. From the OCB-O indicator, as a whole has a high category which means that the insurance agent is willing to comply with the regulations of the insurance company in which they work, the indicator that has the highest average value is that the agent never talks about bad things about the company outside and always adhere to all the company's rules and regulations, while the agency indicators are less actively involved in the activities in the company showed an average value of 3.37 indicates that the agent agent flexible working hours, according to the head of the insurance agent, the activities of insurance agents in the office varies, there is insurance that requires employees to come every morning for a meeting there stating they come at a weekend meeting to do an evaluation and make a plan for the next week. There is an insurance company that states that they are free to come to office to meet supervisornya (no schedule). The indicator that has the lowest average score and with the low category is the agent usually spend hours to talk about things out of work, relax, or play the game means the agent does not spend hours working for things that are not important because basically the agent has a target on his job and must meet clients or customers not to move on to another insurance company.